Pergeseran Paradigma Pengelolaan Kawasan Konservasi: Sebuah Wacana Baru dalam Pengelolaan Kawasan Konservasi - Soekmadi, Rinekso (Department of Forest Resources Conservation and Ecotourism - IPB University, 2003)
Managing protected area in the proper way is one of the most effective effort to conserve the last tropical biodiversity and ecosystems. Nowaday management of protected area faces to many